2011
DOI: 10.5830/cvja-2010-054
|View full text |Cite
|
Sign up to set email alerts
|

The state of heart disease in Sudan : review article

Abstract: Cardiovascular disease (CVD) is the leading cause of mortality worldwide and an important cause of disability. In Africa, the burden of CVD is increasing rapidly and it is now a public health concern. Epidemiological data on diseases is scarce and fragmented on the continent.AimTo review available data on the epidemiology and pattern of heart disease in Sudan.MethodsData were obtained from the Sudan Household Survey (SHHS) 2006, annual health statistical reports of the Sudan Federal Ministry of Health, the STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 31 publications
4
44
0
3
Order By: Relevance
“…It is largely documented that hypertensive heart disease, rheumatic heart disease and cardiomyopathies are the major CVDs in sub-Saharan Africa [9] [11] [12] [13] [14], which is at variance with findings from the Western world where CVDs are largely due to coronary artery disease [15]. Furthermore, CVDs in sub-Saharan Africa are diseases of relatively younger people, with a high early mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is largely documented that hypertensive heart disease, rheumatic heart disease and cardiomyopathies are the major CVDs in sub-Saharan Africa [9] [11] [12] [13] [14], which is at variance with findings from the Western world where CVDs are largely due to coronary artery disease [15]. Furthermore, CVDs in sub-Saharan Africa are diseases of relatively younger people, with a high early mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the prevalence rate of low physical activity was 86.8% in the STEPS survey. 14 Cigarette smoking increases the impact of other risk factors (such as obesity, high cholesterol, diabetes, or older age) on the risk of coronary events. 23 The percentage of patients used tobacco and alcohol are less than those reported in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Large studies for identification of risk factors for cardiovascular disease among Sudanese subjects are not available and most of them are limited to 50-100 subjects.…”
mentioning
confidence: 99%
“…It has been largely eliminated from high-income countries due to increased use of antibiotics coupled with improved living conditions and primary healthcare systems. In Sudan, RHD constitutes one of the major causes of heart disease in children and young adults [1]. Recently, echocardiographic (echo) screening has shown that the prevalence is high in certain areas in Sudan as in North Kordofan (62/1,000) [2].…”
Section: Introductionmentioning
confidence: 99%